Dis/re-orienting design through norm-critical gender lenses: an educational case in Turkey - Yetiş, Erman Örsan; Bakırlıoğlu, Yekta (Frontiers in Sociology, 2024)
Design, as a practice of developing solutions beyond products, and increasingly services and policies, inevitably poses an impact on gender (in)equality which remains largely unrecognised by design practitioners. This paper advocates the urgent need for adopting gender lenses in design education for sustainable cultural transformation through proper recognition of the complexity of any societal and cultural issue, power relations and inequalities, and introduces an initial attempt through a graduate-level educational design project. Throughout the project, students critically reflected on existing orientations in designing to develop norm-critical gender lenses, contained the resultant disorientation emerging from the contrast between their critical approaches and local contexts, and explored novel directions as reorientation to address four different societal and cultural issues and develop eleven design outcomes aiming at gender equality, social justice-oriented empowerment, and cultural transformation. The authors analysed the design processes and outcomes to reveal opportunities and challenges for developing and deploying norm-critical gender lenses in tackling complex, intersecting socio-cultural and political issues, under three themes: gender stereotypes, norms, expectations, and roles; intersectional power relations and inequality embedded in the social structure; and social justice-oriented empowerment beyond the market-oriented individualistic neoliberal order. A shift in the perceptions of the role of designers, from creator/problem-solver to facilitator/participant, and design outcomes, from absolute solutions to intermediaries of sociological and political imaginations, is found crucial in this endeavour, which requires safe spaces for future designers to reflect on existing orientations, contain disorientation with negative capability, and explore novel ways through reorientation.